Spatial equity and cultural participation: how access influences attendance at museums and galleries in London. Issue 1 (2nd January 2016) - Brook, Orian
ABSTRACT: This paper addresses how neighbourhoods operate as opportunity structures for cultural participation, and therefore how unequal access to cultural facilities might influence levels of participation and profiles of participants. The neighbourhood effects literature identifies how where people live shapes their lives, including their participation in various activities, but this has not been applied to cultural participation. Sociological theory explores the importance of social stratification of cultural consumption, but has largely ignored the role of place. In this paper sociological explanations of cultural participation are extended to incorporate the influence of access to cultural infrastructure. An innovative accessibility index for museums and galleries in London, using online searches to weight their attraction, is linked to the Taking Part Survey, and used to predict attendance. Alongside social stratification, significant neighbourhood characteristics are identified, including, importantly, access to museums and galleries. Improved access has a strong positive relationship with attendance, which varies according to qualifications and ethnic group: those with degrees are most likely to attend, but the relationship with access also operates for those with fewer qualifications, who according to traditional explanations have little disposition to attend. The implications of the substantial spatial inequity in investment in museums and galleries are discussed.